1977
DOI: 10.1007/bf01102987
|View full text |Cite
|
Sign up to set email alerts
|

�ber Vorkommen und Bedeutung extra- und intracellul�rer periodisch geb�nderter filament�rer Assoziate

Abstract: Banded fibrous associates are described in the extracellular space of connective tissue from human endometrium, Ehlers-Danlos syndrome and of tendon rupture. In the cases of morbus Dupuytren these associates are also found as intracellular inclusions. The banded structures are interpreted as states of an enzymatically induced degradation of collagen in correlation with Type-III collagen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Recent analysis of an experimental rabbit carcinoma has shown that, during tumour progression, pre-existing long collagen bundles are degraded into thick and wavy cords with frequent loss of cross-striation regularity (Strauli et al, 1983). Similar results have been described in skin carcinoma and in other human pathological conditions, where filamentous material showing a 100-nm pattern, has been observed and interpreted as lytic degradation of the collagen network (Nemetschek-Gansler et al, 1977;Van den Hooff and Tigchelaar-Gutter, 1983). Immunolocalization of collagenases has also been performed on malignant tissues (Woolley, 1982).…”
supporting
confidence: 80%
“…Recent analysis of an experimental rabbit carcinoma has shown that, during tumour progression, pre-existing long collagen bundles are degraded into thick and wavy cords with frequent loss of cross-striation regularity (Strauli et al, 1983). Similar results have been described in skin carcinoma and in other human pathological conditions, where filamentous material showing a 100-nm pattern, has been observed and interpreted as lytic degradation of the collagen network (Nemetschek-Gansler et al, 1977;Van den Hooff and Tigchelaar-Gutter, 1983). Immunolocalization of collagenases has also been performed on malignant tissues (Woolley, 1982).…”
supporting
confidence: 80%
“…The first proposition is more commonly accepted; we agree with it and believe that in our case active phagocytosis and digestion of collagen was taking place. Intracellular banded structures, also called long-spacing fibrils, banded filamentous associates, have been found in Morbus Dupuytren (Gokel & Hubner 1977, Nemetschek-Gansler et al 1977, in recurrent digital fibroma (Bhawan et al 1979), in chondrosarcoma (Imura et al 1975), in cultured tissue (Hentzner & Kobayasi 1979) etc. In some cases these bodies were located inside dilated cisternae connected with the endoplasmic reticulum of fibroblastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…We found intracellular fibers with a normal collagen banding pattern lying free within the cytoplasm of both degenerating and necrotic cells after thallium administration. Intracellular collagen fib e r s -w h e t h e r free, within vacuoles, or in lysosomes--have been described in many tissues of many species [36][37][38][39][40][41][42][43] and have been related to both synthesis and degradation.…”
Section: Bone Of Thallium-treated Chick Embryosmentioning
confidence: 99%